The network software multistep control algorithm based on NNVD research. (2017) - Man, Junfeng; Peng, Cheng; Ma, Yinghui; Li, Changyun
The increasing scale of networked software system not only increases the difficulty to understand and optimise the system, but a small anomaly is more likely to cause the collapse of the whole system. Therefore, in view of the abnormal behaviour of networked software system, this paper proposed a networked software based on network node value degree (NNVD) multistep control algorithm; the algorithm from the perspective of the node path length range to study the spread of the abnormal behaviour of local control, through the network selection to the importance of the control software node, in a scale-free network software system is analysed in local multistep control effectiveness. Studies show that the proposed algorithm can restrain the spread of abnormal behaviour to a certain extent, making exceptions can get effective control in a certain scope.